Protective effect of pogostone on murine norovirus infected-RAW264.7 macrophages through inhibition of NF-κB/NLRP3-dependent pyroptosis. (5th October 2021) - Ye, Qingyan; Ling, Qihua; Shen, Jian; Shi, Lei; Chen, Jianjie; Yang, Tao; Hou, Zhijun; Zhao, Jun; Zhou, Hua
Abstract: Ethnopharmacological relevance: Pogostemon cablin, the dry overground parts of Pogostemon cablin (Blanco) Benth, has been widely used in the treatment of gastrointestinal dysfunction, such as nausea, diarrhea, headaches and fever. Pogostone (PO) is a major component of Pogostemon cablin which has a variety of pharmacological properties, including antiinflammatory, and immunosuppressive activities, and antioxidant. However, the effect of PO on norovirus gastroenteritis and the underlying molecular mechanism remain unclear. Aim of the study: The purpose of our study is to investigate the effects of PO against MNV infection using RAW264.7 cells and to elucidate its active mechanisms. Materials and methods: The cell viability was assessed using Cell Counting Kit-8 (CCK-8) assay and Fluorescein diacetate (FDA) staining. The activation of nuclear factor kappa B (NF-κB) signaling and NOD-like receptor 3 (NLRP3) inflammasome was evaluated by assessing the level of phospho–NF–κB p65, interleukin (IL)-6, TNF-α, NLRP3, cleaved caspase-1, IL-18, IL-1β using Western blot and quantitative real-time PCR (qPCR), respectively. The number of infected cells were determined by immunofluorescence microscopic assay. Results: PO did not possess a cytotoxic effect toward RAW264.7 cells. The cytotoxic damage caused by MNV infection in RAW264.7 cells decreased significantly in the presence of PO. Cell viability assays showed that pyroptosis is the major mechanism of death in MNV-infected RAW264.7 cells. PO could decreased the expression levels of p-p65, IL-6, TNF-α, NLRP3, cleaved caspase-1, IL-1β, and IL-18. Conclusions: These results demonstrate that PO decreases MNV-induced RAW264.7 macrophages death and MNV replication through repressing NF-κB/NLRP3-dependent pyroptosis. Therefore PO may be considered as a potential therapeutic agent for preventing and treating norovirus gastroenteritis. Graphical abstract: Image 1